Beyond refuge : a framework for the emancipatory education of forcibly-displaced youth - Swisher, Jason R. (Emerald Publishing Limited, 2023)
As the record number of forcibly-displaced persons in the world continues to rise, more people of differing origins are sharing space and learning to live together. Prolonged displacement has turned into permanent resettlement and citizenship. To reflect this geopolitical transformation, education too must transform. Beyond Refuge explores abstractions, practicalities, impediments, and assets proffered by research participants to illustrate what an educational transformation should and could look like via a theoretical framework for emancipatory education of forcibly-displaced youth. Interviews, focus groups, and participant observations gather data from participants across local, state, national, and international levels of educational influence, resulting in a collection of diverse perspectives. The results of Swisher's study are presented in narratives and discussions upon which educational leaders can build. An emancipatory education of forcibly-displaced youth must begin with an examination of ourselves, our systems, and our societies and be sustained by leadership, policies, and practices based in love, empathy, listening, learning, and community. A central text for the next steps in inclusive and equitable education, Beyond Refuge appeals to researchers, teachers, leaders, community figures and participants, and policymakers wanting to create lasting and impactful change in their local and national societies.
Keywords: Refugee children -- Education.; Education -- General.; Organization & management of education.; elektronické knihy; electronic books